2015
DOI: 10.1186/s12934-015-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the 2-acyl-glycerophosphoethanolamine cycle improve glucose metabolism in Escherichia coli strains employed for overproduction of aromatic compounds

Abstract: BackgroundAs a metabolic engineering tool, an adaptive laboratory evolution (ALE) experiment was performed to increase the specific growth rate (µ) in an Escherichia coli strain lacking PTS, originally engineered to increase the availability of intracellular phosphoenolpyruvate and redirect to the aromatic biosynthesis pathway. As result, several evolved strains increased their growth fitness on glucose as the only carbon source. Two of these clones isolated at 120 and 200 h during the experiment, increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The same reproducible expression level of this gene was detected in all the strains in the conditions (EXP and STA growth phases) in which bacteria were grown and sampled from SA-producing cultures since this is the most important characteristic that a reference gene should have in accordance with the MIQE guidelines. Values for ihfB gene detected for the utilized strains demonstrate the stability of the expression of this reference gene in all the analyzed derivatives for the used conditions in this report and also in previous reports (data not shown) [Flores et al, 2005[Flores et al, , 2007[Flores et al, , 2008Aguilar et al, 2012Aguilar et al, , 2015.…”
Section: Transcriptomic Analysis By Rt-pcrmentioning
confidence: 50%
“…The same reproducible expression level of this gene was detected in all the strains in the conditions (EXP and STA growth phases) in which bacteria were grown and sampled from SA-producing cultures since this is the most important characteristic that a reference gene should have in accordance with the MIQE guidelines. Values for ihfB gene detected for the utilized strains demonstrate the stability of the expression of this reference gene in all the analyzed derivatives for the used conditions in this report and also in previous reports (data not shown) [Flores et al, 2005[Flores et al, , 2007[Flores et al, , 2008Aguilar et al, 2012Aguilar et al, , 2015.…”
Section: Transcriptomic Analysis By Rt-pcrmentioning
confidence: 50%
“…Genotoxicity studies exhibited the highest prevalence of inappropriate methods' usage (88.9%), largely due to the dominant influence of the Ames test in this field, as we correctly anticipated. Interestingly, only two articles in the genotoxicity category reported the use of appropriate methods, and they are from groups mostly working in the areas of DNA repair and in evolutionary genetics [123,155]. Stacked areas depict the proportion of the selected studies employing specific methods or method families.…”
Section: Inappropriate Methods Are Still Widespread But Their Prevale...mentioning
confidence: 99%
“…Shen et al, 2020). Aguilar et al (2012Aguilar et al ( , 2015 reported that deletion of the 2-acyl-glycerophosphoethanolamine cycle allows fast growth in glucose and improves the production of aromatic compounds in E. coli strain lacking the phosphoenolpyruvate: carbohydrate phosphotransferase system (PTS). The 2-acylglycerophosphoethanolamine cycle comprises 12 contiguous genes (rppH, ygdT, mutH, ygdQ, ygdR, tas, lplT, aas, omrB, and part of ptsP and galR, 10,328 bp).…”
Section: Host Strain Engineering Increasing the Availability Of L-tyrosinementioning
confidence: 99%
“…The 2-acylglycerophosphoethanolamine cycle comprises 12 contiguous genes (rppH, ygdT, mutH, ygdQ, ygdR, tas, lplT, aas, omrB, and part of ptsP and galR, 10,328 bp). This growth advantage may be the increase of mRNA levels of glycolytic genes due to RppH pyrophosphohydrolase activity deficiency and the increased glucose uptake through GalP because of the lack of GalR (Aguilar et al, 2012(Aguilar et al, , 2015. The starting strain E. coli TYR-30 in this study is a derivative of E. coli DOPA-30N which is lacking PTS (Wei et al, 2016).…”
Section: Host Strain Engineering Increasing the Availability Of L-tyrosinementioning
confidence: 99%